Role of nitric oxide and beta-adrenoceptors of the central nervous system on the salivary flow induced by pilocarpine injection into the lateral ventricle - Saad, W. A.; Guarda, IFMS; Guarda, R. S.; Camargo, LAD; dos Santos, TAFB; Simoes, S. (Elsevier B.V., 2002)
Our studies have focused on the effect of L-NG-nitroarginine methyl ester (L-NAME), an inhibitor of nitric oxide synthase (NOS), and L-arginine, the substrate of NOS, on salivary secretion induced by the administration of pilocarpine into the lateral cerebral ventricle (LV) of rats. The present study has also investigated the role of the beta-adrenergic agonists and antagonist injected into LV on the salivary secretion elicited by the injection of pilocarpine into LV. Male Holtzmann rats with a stainless-steel cannula implanted into the LV were used. The amount of salivary secretion was studied over a 7-min period after injection of pilocarpine, isoproterenol, propranolol, salbutamol, salmeterol, L-NAME and L-arginine. The injection of pilocarpine (10, 20, 40, 80 and 160 mug/mul) into LV produced a dose-dependent increase in salivary secretion. The injection of L-NAME (40 mug/mul) into LV alone produced an increase in salivary secretion. The injection of L-NAME into LV previous to the injection of pilocarpine produced an increase in salivary secretion. L-Arginine (30 mug/mul) injected alone into LV produced no change in salivary secretion. L-Arginine injected into LV attenuated pilocarpine-induced salivary secretion. The isoproterenol (40 nmol/mul) injected into LV increased into LV increased the salivary secretion. When injected previous to pilocarpine at a dose of 20 and 40 mug/mul, isoproterenol produced and additive effect on pilocarpine-induced salivary secretion. The 40-nmol/mul dose of propranolol injected alone or previous to pilocarpine into LV attenuated the pilocarpine-induced salivary secretion. The injection of salbutamol (40 nmol/mul), a specific beta-2 agonist, injected alone into LV produced no change in salivary secretion and when injected previous to pilocarpine produced and increase in salivary secretion. The 40-nmol/mul dose of salmeterol, a long-acting beta-2 agonist, injected into LV alone or previous to pilocarpine produced no change in salivary secretion. The results have shown that central injections of L-NAME and L-arginine interfere with the salivary secretion, which implies that might participate in pilocarpine-induced salivary secretion. The interaction between cholinergic and beta-adrenergic receptors of the central nervous system (CNS) for the control of salivary secretion can also be postulated. (C) 2002 Elsevier B.V. All rights reserved.
Keywords: CNS; nitric oxide; beta-adrenoceptors; pilocarpine; salivary secretion